MENGEKSPLORASI EFEKTIVITAS MEDIA PEMBELAJARAN BERBASIS ALAM TERHADAP KETERLIBATAN DAN PRESTASI AKADEMIK SISWA: STUDI KASUS DI SMP NEGERI 1 PRONOJIWO (Education Journal : Journal Educational Research and Development, 2022)
This study aims to explore the effectiveness of nature-based learning media on student engagement and academic achievement in SMP Negeri 1 Pronojiwo. The research method used is quasi-experimental with a pretest-posttest control group design. The study subjects consisted of 60 seventh-grade students selected by purposive sampling. Data was collected using a questionnaire on student engagement in learning and academic achievement tests. The results showed that nature-based learning media is effective in improving student engagement and academic achievement in SMP Negeri 1 Pronojiwo. Additionally, there is a positive relationship between student engagement in learning and academic achievement in learning with nature-based learning media. This study provides important implications for the development of more innovative and effective learning media in improving the quality of learning.